RESULTS OF FUNCTIONING OF PUBLIC UNIVERSITIES: ESTABLISHING A SET OF RATIOS PROVIDING RELIABLE MANAGEMENT INFORMATION BASED ON DATA DERIVED FROM AN ENTITY'S REPORTS - Jarosław Karpacz; Aleksandra Pisarska (Polityki Europejskie, Finanse i Marketing)
The aim of the study is to define a set of ratios, enabling multidimensional assessment of the activity of public universities as units of the public finance sector, in order to improve theefficiency of their management. The selection of appropriate ratios, which are also highly reliable in relation to occurring phenomena and processes, becomes a useful management tool. Hence, thecontent of the study includes a comprehensive measurement of a university's results. Empirical research was conducted at a deliberately selected multi-disciplinary university, i.e. an entityconducting research and didactic activities in many fields of science. The empirical material was collected using information derived from financial statements and analytical information from theaccounting books of the analyzed entity. The study covered the years from 2015 to 2019. The conducted empirical research provided evidence in the light of which the developed set of ratioshas a high management usefulness, as it allowed to assess the state of processes taking place in the examined unit.